Structures and electronic properties of Mo2nNn （n=1-5）： a density functional study - 陈杭 雷雪玲 刘立仁 刘志锋 祝恒江 (Chinese physics B, 2010)
The lowest-energy structures and the electronic properties of Mo2nNn （n=1-5） clusters have been studied by using the density functional theory （DFT） simulating package DMol3 in the generalized gradient approximation （GGA）. The resulting equilibrium geometries show that the lowest-energy structures are dominated by central cores which correspond to the ground states of Mon （n = 2, 4, 6, 8, 10） clusters and nitrogen atoms which surround these cores. The average binding energy, the adiabatic electron affinity （AEA）, the vertical electron affinity （VEA）, the adiabatic ionization potential （AIP） and the vertical ionization potential （VIP） of Mo2nNn （n=1-5） clusters have been estimated. The HOMO LUMO gaps reveal that the clusters have strong chemical activities. An analysis of Mulliken charge distribution shows that charge-transfer moves from Mo atoms to N atoms and increases with cluster size.